THE ROLE OF SULTAN HAMENGKU BUWONO IX IN UPHOLDING INDONESIAN INDEPENDENCE IN 1945-1950 - Ony Widiarto; Sugiyanto Sugiyanto; Marjono Marjono (History Education, University of Jember, 2020)
The background of this research is after the Indonesian nation became independent until the change of form of the Indonesian state which was originally since KMB (Konferensi Meja Bundar) is a federal state back into the form of unitary state (1945-1950). Indonesia's chaotic condition in the social, political and economic fields prompted Sultan Hamengku Buwono IX to apply the rescue action of the Republic of Indonesia. This study aims to (1) examine the background of Hamengku Buwono IX in maintaining the independence of the Republic of Indonesia; (2) to examine in depth the actions or strategies of Hamengku Buwono IX in maintaining the independence of the Republic of Indonesia in 1945-1950. This study uses historical research methods with heuristic steps, criticism, interpretation, and historiography. Sultan Hamengku Buwono IX retained the independence of the Republic of Indonesia, preventing the Dutch crime in Jakarta, which moved the capital in Yogyakarta. When the capital of Yogyakarta in the attack of Sultan Hamengku Buwono IX, became a savior and dared to arrange a counterattack. Sultan Hamengkubuwono IX accelerated the process of recognition of Indonesian independence. However, a new problem arose in the form of Westerling insurrection and Sultan Hamid II. Sultan Hamengkubuwono IX managed to prevent and make people not believe in the federalists. This is what makes the return of the state form into a unitary state. Keywords: Sultan, Defend, Independence, Republic Indonesia.